2008
DOI: 10.5334/pb-48-2-3-109
|View full text |Cite
|
Sign up to set email alerts
|

How Attributes of the Feedback Message affect Subsequent Feedback Seeking: The interactive effects of feedback sign and type

Abstract: In the current study, we examined the interactive effects of feedback type and sign on feedback-seeking behaviour, as well as the moderating role of regulatory focus. Using a behavioural measure of feedback seeking, we demonstrated a strong interaction between feedback type and sign, such that individuals subsequently sought the most feedback after they were provided with negative process feedback. Additionally, results suggested that an individual's chronic regulatory focus has implications for his or her fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Overall, this research-using a global sample of 235 leaders-shows that contrary to a lot of popular opinion, people really want to receive more negative feedback from their own bosses than they are actually getting. This fi nding is also in line with scholarly work that previously found individuals are motivated by both positive and negative feedback (Medvedeff et al, 2008). Specifi cally, we found that individuals would prefer to get a little less positive outcome feedback (i.e., "Good job") and a little more of both negative outcome and negative process.…”
Section: So What?supporting
confidence: 91%
See 1 more Smart Citation
“…Overall, this research-using a global sample of 235 leaders-shows that contrary to a lot of popular opinion, people really want to receive more negative feedback from their own bosses than they are actually getting. This fi nding is also in line with scholarly work that previously found individuals are motivated by both positive and negative feedback (Medvedeff et al, 2008). Specifi cally, we found that individuals would prefer to get a little less positive outcome feedback (i.e., "Good job") and a little more of both negative outcome and negative process.…”
Section: So What?supporting
confidence: 91%
“…Many people assume that feedback is just being told that you did a good job on a task or that you did poorly on something. Yet, researchers at the University of Akron have found that feedback involves more than just a simple evaluation of whether someone performed well or poorly (Medvedeff , Gregory, & Levy, 2008). Specifi cally, there are four types of feedback that employees can receive on their work performance:…”
Section: What Is Feedback and Why Is It Important?mentioning
confidence: 99%
“…To ensure that the feedback was perceived as equally negative across conditions, the sign of leader feedback was measured using two items originally used in a laboratory study by Medvedeff, Gregory, and Levy (). An example item is ‘In general, the feedback I received informed me that my performance was unsatisfactory’ (α = .81 and .82 after Introduction and Manipulation, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of feedback is also influenced by whether the feedback is based on the outcome of the behaviour or the process by which the outcome is changed. 7 Outcome based feedback provides information about the end result. For an individual with the goal of losing weight, the outcome measure is body weight as it changes over time.…”
Section: Penny Deck Simon Fraser Universitymentioning
confidence: 99%